СОВРЕМЕННЫЕ ОБРАЗОВАТЕЛЬНЫЕ ТЕХНОЛОГИИ КАК ЗАЛОГ МОДЕРНИЗАЦИИ ПРОЦЕССА ПРЕПОДАВАНИЯ ПРЕДМЕТА “ФИЗИЧЕСКАЯ КУЛЬТУРА” - Артак Гарникович Степанян (International Journal of Innovative Technologies in Social Science, 2019)
The article considers the peculiarities of modern educational technologies using at “Physical Training” lessons. The results of theoretical analysis and practical work show that the use of these technologies will make the teaching process more effective. The use of didactic materials and creative approach to the teaching process will increase and enrich the content of the subject, improve the quality of the lessons and contribute to the involvement of schoolchildren in physical culture and sports.